Different Pigmentation Risk Loci for High-Risk Monosomy 3 and Low-Risk Disomy 3 Uveal Melanomas. (23rd August 2021) - Mobuchon, Lenha; Derrien, Anne-Céline; Houy, Alexandre; Verrier, Thibault; Pierron, Gaëlle; Cassoux, Nathalie; Milder, Maud; Deleuze, Jean-François; Boland, Anne; Scelo, Ghislaine; Cancel-Tassin, Géraldine; Cussenot, Olivier; et al.
Abstract: Background: Uveal melanoma (UM), a rare malignant tumor of the eye, is predominantly observed in populations of European ancestry. UMs carrying a monosomy 3 (M3) frequently relapse mainly in the liver, whereas UMs with disomy 3 (D3) are associated with more favorable outcome. Here, we explored the UM genetic predisposition factors in a large genome-wide association study (GWAS) of 1142 European UM patients and 882 healthy controls . Methods: We combined 2 independent datasets (Global Screening Array) with the dataset described in a previously published GWAS in UM (Omni5 array), which were imputed separately and subsequently merged. Patients were stratified according to their chromosome 3 status, and identified UM risk loci were tested for differential association with M3 or D3 subgroups. All statistical tests were 2-sided. Results: We recapitulated the previously identified risk locus on chromosome 5 on CLPTM1L (rs421284: odds ratio [OR] =1.58, 95% confidence interval [CI] = 1.35 to 1.86; P  =   1.98 × 10 -8 ) and identified 2 additional risk loci involved in eye pigmentation: IRF4 locus on chromosome 6 (rs12203592: OR = 1.76, 95% CI = 1.44 to 2.16; P  =   3.55 × 10 -8 ) and HERC2 locus on chromosome 15 (rs12913832: OR= 0.57, 95% CI = 0.48 to 0.67; P  =   1.88 × 10 -11 ). The IRF4 rs12203592 single-nucleotide polymorphism was found to be exclusively associated with risk for the D3 UM subtype (ORD3 = 2.73, 95% CI = 1.87 to 3.97; P  =   1.78 × 10 -7 ), and the HERC2 rs12913832 single-nucleotide polymorphism was exclusively associated with risk for the M3 UM subtype (ORM3 = 2.43, 95% CI = 1.79 to 3.29; P  =   1.13 × 10 -8 ). However, the CLPTM1L risk locus was equally statistically significant in both subgroups. Conclusions: This work identified 2 additional UM risk loci known for their role in pigmentation. Importantly, we demonstrate that UM tumor biology and metastatic potential are influenced by patients' genetic backgrounds.